GAMBARAN PENGETAHUAN DAN SIKAP SISWA TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT DENGAN CUCI TANGAN PAKAI SABUN DI YAYASAN PERGURUAN TUT WURI HANDAYANI DI MABAR KECAMATAN MEDAN DELI TAHUN 2014 - winda sari; Alam Bakti Keloko; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Illumination about hand washing using soap is one of Clean and Healthy Living Behavior (PHBS) and has been the world concern, it has because the problem of the lack of hand washing behavior practice occurs in not only developing countries but also developed ones most people still forget FOR perform Hand Washing Behavior. The correct hand washing reduces the incidence of disease. To describe the behavior of elementary school students about Behavior Clean and Healthy with counseling Handwashing in Foundation Tut Wuri Handayani at Medan Mabar.This research is descriptive-analitic cross sectional. The object of research was the IV graders as much as 33 people and school guard, teacher and principal.Results of univariate analysis are better knowledge, attitudes and actions strongly agree sometimes. Then concluded that there is a picture of the extension services PHBS wash hands on knowledge, attitudes, and actions of the students wash their hands, guards, teachers and principals.It is recommended to provide education on an ongoing basis through UKS program of the school.